2019
DOI: 10.1017/s0022215119000756
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial contamination of surgical loupes and headlights

Abstract: BackgroundMedical equipment can transmit pathogenic bacteria to patients. This single-institution point prevalence study aimed to characterise the types and relative amount of bacteria found on surgical loupes, headlights and their battery packs.MethodSurgical loupes, headlights and battery packs of 16 otolaryngology staff and residents were sampled, cultured and quantified. Plate scores were summed for each equipment type, and the total was divided by the number of users to generate mean bacterial burden scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
(20 reference statements)
1
2
0
Order By: Relevance
“…Moreover, the discrepancy could be due to variation in the study setting, selection of appropriate cleaning and disinfecting products, disinfectant kill time, and existing infection prevention and control strategies [51]. The present finding is comparable with the study conducted on bacterial contamination of an operating theatre in Nigeria [62] with contamination of 78%, a study in Iran [21] on microbial contamination of keyboards and electronic equipment of ICU (n = 76) showing a 76% contamination rate of computer keyboards and electronic devices, a study conducted in India [60] to assess the bacterial contamination of stethoscope diaphragms (n = 200) sampled from HCWs (79%), a study in Canada [63] on bacterial contamination of surgical loupes (68.75%), and a study in Sri Lanka [64] conducted to assess anesthetist personal mobile phones and wristwatch bacterial contamination during theatre sessions (70%). Also, a lower prevalence of bacterial contamination of inanimate surfaces and equipment compared to the present finding was reported including a study (2009-2015) done in Egypt [65] to assess bacteriology of inanimate surfaces and equipment among selected hospitals which report a prevalence of 25.6% and studies from India [66,67] aimed at evaluating bacterial contamination from clinical inert environment (n = 100) and cell phone of HCW (=30) which report 38% and 42.8% of contamination, respectively.…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, the discrepancy could be due to variation in the study setting, selection of appropriate cleaning and disinfecting products, disinfectant kill time, and existing infection prevention and control strategies [51]. The present finding is comparable with the study conducted on bacterial contamination of an operating theatre in Nigeria [62] with contamination of 78%, a study in Iran [21] on microbial contamination of keyboards and electronic equipment of ICU (n = 76) showing a 76% contamination rate of computer keyboards and electronic devices, a study conducted in India [60] to assess the bacterial contamination of stethoscope diaphragms (n = 200) sampled from HCWs (79%), a study in Canada [63] on bacterial contamination of surgical loupes (68.75%), and a study in Sri Lanka [64] conducted to assess anesthetist personal mobile phones and wristwatch bacterial contamination during theatre sessions (70%). Also, a lower prevalence of bacterial contamination of inanimate surfaces and equipment compared to the present finding was reported including a study (2009-2015) done in Egypt [65] to assess bacteriology of inanimate surfaces and equipment among selected hospitals which report a prevalence of 25.6% and studies from India [66,67] aimed at evaluating bacterial contamination from clinical inert environment (n = 100) and cell phone of HCW (=30) which report 38% and 42.8% of contamination, respectively.…”
Section: Discussionsupporting
confidence: 82%
“…It was also evident there were proponents of loupes and those who were less enthusiastic (Table 3). Another potential negative factor is that recent study has demonstrated that loupes can act as a surface for microbes—however there is insufficient evidence to suggest that this could be linked to increased surgical site infections 21,22 . Nevertheless, routine cleaning of loupes should be recommended.…”
Section: Discussionmentioning
confidence: 99%
“…It is an oxidase-positive, catalase-positive, and aerobic Gram-negative coccobacillus known to be pathogenic to the mollusc, using a nematode as a vehicle [5]. M. osloensis has been isolated from environmental sources in hospitals [6], from the normal human respiratory tract [7], and from ocular infections (conjunctivitis, keratitis) [8,9]. Except for its role as an ocular bacterial pathogen, it is a rare cause of infection and is usually considered a contaminant by most clinical laboratories.…”
Section: Discussionmentioning
confidence: 99%